Immune Cell Infiltration and Relevant Gene Signatures in the Tumor Microenvironment that Significantly Associates With the Prognosis of Patients With Breast Cancer - Xu, Qiang; Yan, Xinghe; Han, Zhezhu; Jin, Xiuying; Jin, Yongmin; Sun, Honghua; Liang, Junhua; Zhang, Songnan (Frontiers in Molecular Biosciences, 2022)
Breast cancer is the most common malignancy and the leading cause of cancer-related deaths in women. Recent studies have investigated the prognostic value of the tumor microenvironment (TME)-related genes in breast cancer. This study aimed to identify the immune-related prognostic signature for breast cancer and evaluate the probability their prognostic value adds to the current staging system. In this study, we comprehensively estimated the TME infiltration patterns of 1077 breast cancer patients downloaded from TCGA by applying the ssGSEA method to the RNA-sequencing of these patients, thus, two immune cell infiltration clusters were generated. Based on the immune cell infiltration cluster, we found 983 common differentially expressed genes using the limma algorithm. In addition, GSEA indicated some pathways with remarkable enrichment in two immune cell infiltration clusters that may be helpful in understanding the potential mechanisms. Finally, we identified seven immune-related genes with survival as prognostic signatures by using univariate Cox, survival and LASSO analyses and constructed a TME score. The prognostic value of the TME score was self-validated in the TCGA cohort and further validated in an external independent set by time-dependent survival receiver operation. Univariate and multivariate analyses of with clinicopathological characteristics revealed that the TME score was an independent prognostic factor. In conclusion, the proposed TME score model should be considered as a prognostic factor, similar to current TNM stage, and the seven immune-related genes can be a potential biomarker for breast cancer.